Establishing a novel model of malignant airway stenosis in rabbit - Lin, Xiaoxiao; Zhou, Liqin; Zhou, Wanting; Li, Yuping; Jin, Xuru; Ye, Min; Chen, Chengshui (Frontiers in Oncology, 2022)
Background Malignant central airway stenosis is a life-threatening condition. However, treatment of malignant airway stenosis remains challenging. There is currently a severe lack of an excellent animal model of malignant airway stenosis to facilitate treatment approaches. This is the first study to establish a rabbit model of malignant airway stenosis for bronchoscopic interventional studies. Materials and methods New Zealand White rabbits were used in this study, randomly divided into group A (18 rabbits) and group B (6 rabbits). A VX2 fragment suspension was injected into the submucosal layer of rabbits’ airway by bronchoscopy. Bronchoscopic examinations were performed once a week after VX2 tumor implantation to observe tumor growth and the degree of airway stenosis. Randomly, three rabbits were generally dissected after a weekly bronchoscopic examination in group A. The rabbits that reached grade III airway stenosis underwent stent implantation in group B. Results A total of 24 rabbits were successfully implanted with the VX2 fragment suspension in the airway without significant adverse events, and the success rate of the tumor growth was 100%. The degree of airway stenosis reaching grade III took 2 to 3 weeks after implantation of the VX2 tumor. The median survival time of rabbit models without stent implantation and rabbits with stent implantation was 32.5 and 32.0 days, respectively. Conclusions The implanting method is safe and effective for the establishment of a rabbit model of malignant airway stenosis. When the tumor grows to 2 to 3 weeks, the rabbit model is available for stent implantation. We recommend the models for more preclinical animal studies on bronchoscopic interventional treatments.